The Effect of Organizational Culture and Internal Supervision on the Performance of Health Workers - Harefa, Karnirius (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Health worker performance is a key element in the success of primary healthcare services at Puskesmas. A strong organizational culture and effective internal supervision are believed to enhance motivation, productivity, and service quality among health workers. Objective: This study aims to analyze the effect of organizational culture and internal supervision on the performance of health workers at Bandar Khalifah Health Center, Percut Sei Tuan District. Methods: This research employed an analytical quantitative approach with a cross-sectional design. The population consisted of all active health workers (n=58), selected through total sampling. Data were collected via structured questionnaires and analyzed using Spearman correlation and multiple logistic regression. Results: Findings indicated that organizational culture and internal supervision simultaneously had a significant influence on health worker performance (p<0.05), explaining 63.7% of performance variation. Organizational culture showed a greater effect (Exp(B)=5.66) compared to internal supervision (Exp(B)=3.64). Conclusion: Positive organizational culture and structured internal supervision significantly improve health worker performance. It is recommended that management enhance teamwork values, provide leadership training, and ensure consistent, participative supervision practices.